Mekanisme Mempertahankan Teritori dalam Suatu Wilayah - Parmonangan Manurung; Ikaputra Ikaputra (TATALOKA, 2020)
Territoriality is a term that was initially used to describe the realm of power in animals, especially birds. In its development, this terminology is also used to define areas owned by humans, both individuals, and groups. This study aims to find the process and mechanism of forming territorial areas in built environments, as well as the defense system used, both on a micro and macro scale. The study was conducted using a content analysis method with the object of research being various texts related to "territoriality" and research subjects in the form of books and articles published in journals. The results showed that there is a process of an area into a territory, which has the resources to meet the needs, the process of ownership or control of the area, as well as the process of maintaining an area using a particular defense system. From the results of the discussion, it can be concluded that the territory is owned and managed to secure resources, and efforts to maintain the territory are carried out with one or several defense systems.